Pengaruh Lingkungan Keluarga, Kepribadian, dan Peluang Usaha Terhadap Minat Berwirausaha Mahasiswa Pendidikan Administrasi Perkantoran 2022 - Dewi Fitriyani; Dian Fithra Permana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study aims to identify the following factors: the influence of the family environment on students' entrepreneurial interests; the influence of personality on students' entrepreneurial interests; and the influence of business opportunities on students' entrepreneurial interests. This study took a population of 133 students of the Office Administration Education Study Program Class of 2022, Semarang State University. Calculation The number of samples uses the proportional random sampling technique using the slovin formula for 100 students. Using an associative quantitative research approach. The data collected uses validity and reliability tests. Using multiple linear regression analysis with the prerequisites of classical assumption tests: normality test, multicollinearity test, linearity test, and heteroscedasticity test. Hypothesis testing uses determination coefficients, F test, and t test. This study found that independent variables and bound variables had a significant effect on each other obtained on hypothesis testing using multiple linear regression analysis. With a significance level of 0.000, the variables of family environment and business opportunities have a significant impact on entrepreneurial interest, while the personality variable has a significant impact on entrepreneurial interest with a significance level of 0.003.